The best gift of all - Emmett, Jonathan (London, Walker books Ltd, 2008)
It's autumn, and the weather is so awful that Mole hasn't been able to visit Rabbit for days. He's just beginning to worry about her, when suddenly he thinks of a plan. He doesn't have to go out in the rain at all - he can dig a tunnel. With his friends behind him, Mole digs his way into Rabbit's burrow and finds her in bed with a terrible cold.